Recycling oil-extracted microalgal biomass residues into nano/micro hierarchical Sn/C composite anode materials for lithium-ion batteries. (1st October 2017) - Song, Danoh; Park, Jinseok; Kim, Kyuman; Lee, Lee Seol; Seo, Jung Yoon; Oh, You-Kwan; Kim, Yong-Joo; Ryou, Myung-Hyun; Lee, Yong Min; Lee, Kyubock
Graphical abstract: Highlights: Nano/micro hierarchical Sn/C anode materials are prepared from biomass residues. Oil-extraction process guarantees a cost-effective synthesis strategy. Oil-extraction process provides nano/micro hierarchical Sn/C anode materials. Nano/micro hierarchical Sn/C anode materials show improved rate capability. Abstract: We introduce a novel approach for the high-value production of nano/micro hierarchical structured Sn anodes for lithium-ion batteries (LIBs) by utilizing microalgal biomass residues that collaterally form during oil extraction for biofuel production. The Sn/C composites made from the oil-extracted microalgal biomass residues (the extracted Sn/C) exhibit the following advantages as high-energy-density anodes: 1) a homogeneous distribution of Sn nanoparticles in the carbon matrix (Sn/C), which efficiently relieves the strain caused by volume changes of the active materials; 2) a high porosity of Sn/C composites; and 3) a homogeneous distribution of the hetero elements N and P in the carbon matrix. Overall, the extracted Sn/C exhibit improved electrochemical performance in LIBs compared with the Sn/C composites made from the microalgal biomass residues without oil extraction (non-extracted Sn/C). The extracted Sn/C have improved rate capabilities (160.0 and 72.9 mAh g −1 for the extracted Sn/C and the non-extracted Sn/C, respectively, at the 80th cycle, 3.5 A g −1 ) and improved cycle performances (511.7 and 493.2 mAh g −1 for the extracted Sn/C and the non-extracted Sn/C, respectively, at the 300th cycle, 200 mA g −1 ).